Agriculture Database Image Content Attributes Storage and Retrieval Design for Paddy Insect - Airuddin, Ahmad (2006)
Storing and retrieving the image and its associated information of paddy insects can be useful to Malaysia especially who required information about paddy insects. As Malaysia is focusing on agriculture, there must be technology provided in this field. In this study, the prototype of database design developed with a method of choosing the attributes, and this technique described by the content of image to achieve the suitable image storage and retrieval and enable effective in indexing image database for online paddy insects. Through the Internet online prototype, the end user can get the information of paddy insects and they also can see the image of paddy insect by using search engine that provided in this prototype. There are two types of search engine provided which are using Structured Query Language (SQL) and Fuzzy Logic. The prototype is also provides the administrator to add, search, update and delete information of paddy insects.